2011
DOI: 10.1002/bdra.20833
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated repression of β-catenin and its transcriptional signaling mediates neural crest cell death in an avian model of fetal alcohol syndrome

Abstract: Fetal Alcohol Syndrome (FAS) is a common birth defect in many societies. Affected individuals have neurodevelopmental disabilities and a distinctive craniofacial dysmorphology. These latter deficits originate during early development from the ethanol-mediated apoptotic depletion of cranial facial progenitors, a population known as the neural crest. We showed previously that this apoptosis is caused because acute ethanol exposure activates a G protein-dependent intracellular calcium within cranial neural crest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 61 publications
5
73
0
Order By: Relevance
“…In both chicken and zebrafish, Flentke et al have shown that this ethanol-induced death is calcium and CaMKII dependent. 28,72 Collectively, these findings suggest that the mechanisms of facial deformity in FASD are conserved across vertebrates.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 85%
“…In both chicken and zebrafish, Flentke et al have shown that this ethanol-induced death is calcium and CaMKII dependent. 28,72 Collectively, these findings suggest that the mechanisms of facial deformity in FASD are conserved across vertebrates.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 85%
“…Neural crest progenitors are induced immediately lateral to the neural plate, and thus a smaller prechordal and neural plate would also reduce the neural crest population size. Work in chick supports this mechanism, as gastrulation-stage exposure (50 mM, 20 mg/egg) reduces the expression of early neural crest markers including foxd3, wnt6 and snai2 (Flentke et al 2011), suggesting their suppressed induction and/or population shortfall.…”
Section: Mechanistic Insights From Avian Models Of Fasdmentioning
confidence: 95%
“…Inhibition of other calcium-dependent kinases including protein kinase C and CaMKIV was ineffectual against alcohol, showing the pathway’s specificity. Ellies et al (2000) previously showed that the programmed cell death within a subset of neural crest progenitors depends on a non-canonical Wnt effector, and, following this lead, Flentke et al (2011) found that alcohol destabilizes β-catenin and its Wnt-dependent transcriptional activity within neural crest cells. The β-catenin destabilization is calcium-dependent and mediated not by known Wnt effectors including GSK3β and calpain, but rather by CaMKII (Flentke et al 2014).…”
Section: Mechanistic Insights From Avian Models Of Fasdmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to drugs or environmental chemicals can cause abnormal migration, differentiation, division or survival of NC cells and can contribute to multiple pathologies (Chen and Sulik, 2000;Garic-Stankovic et al, 2006;Wentzel and Eriksson, 2009;Flentke et al, 2011;Garic et al, 2011). Understanding the effects of bentonite on NC stem cells can help to prevent many NC-derived pathologies.…”
Section: Introductionmentioning
confidence: 99%